Evaluasi implementasi kuriulum 2013 di SD Negeri Karangrejek II Wonosari Gunungkidul Daerah Istimewa Yogyakarta - Tunjung Eka Putra (Universitas Sarjanawiyata Tamansiswa, 2016)
This study is aimed at (1) finding out the suitability of the curriculum in SD Negeri Karangrejek II with the arrangement guide of 2013 curriculum, (2) finding out the suitability of the learning program planning of2013 curriculum, (3) finding out the suitability of learning process implementation in 2013 curriculum,(4) finding out the suitability of the learning result evaluation in 2013 curriculum, and (5) finding out the obstructing factors of the implementation of 2013 curriculum in SD Negeri Karangrejek II Wonosari, Gunungkidul, Daerah Istimewa Yogyakarta. This research is included in the evaluation with distance model. The implementation measurement is done by comparing the ideal condition with the real condition about the standard implementation of 2013 curriculum. The data in this research is collected by using document study in the curriculum, learning plans (syllabus and lesson plan), and evaluation; conducting an observation on the learning implementation components, and some interviews on the obstructing factors. The data collection can be classified into two categories, which are the interactive model and non-interactive model. The interactive technique consists of interviews and observations, while the non-interactive technique consists of analysis, documents, and archives. From the research result, it is concluded that the implementation of the 2013 curriculum in SD Negeri Karangrejek II Wonosari, Gunungkidul, Yogyakarta is suitable to the implementation standard of 2013 curriculum. The curriculum in SD Negeri Karangrejek II has been composed based on the KTSP curriculum arrangement guide. The learning plans (syllabus and lesson plan) are composed by the teachers who are trained about the process standard of 2013 curriculum. The learning processes conducted by the teachers are not optimum in using the integrative theme approach and scientific approach. The evaluations on attitudes, knowledge, and skills done by the teacher are not carried out well, especially on attitude and skills evaluation. The obstruction of the 2013 curriculum is that the training material is not suitable yet with the curriculum implementation, the difficulties in carrying out the themed curriculum, the evaluation procedures which are still very complex, daily test, mid-semester test, and semester test became the scores in the final report.